If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 5 = 13 Reorder the terms: 5 + 2s = 13 Solving 5 + 2s = 13 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2s = 13 + -5 Combine like terms: 5 + -5 = 0 0 + 2s = 13 + -5 2s = 13 + -5 Combine like terms: 13 + -5 = 8 2s = 8 Divide each side by '2'. s = 4 Simplifying s = 4
| 6/5/2/15 | | 2w^2+9w-4-w^2-8w-16=0 | | 4(2x+5)=35 | | 30+10x=10x+10 | | (x)=-16x^2+46x+6 | | 6x-3/10=9 | | x+x+25+3x-39=816 | | =-16x^2+46x+6 | | 2/17*14 | | v^2=22v-21 | | 2*7/5=60 | | ln(2x^2/x)=1.13 | | 30x^2-53x+21=0 | | =5x^3-20x^2-5x+20 | | 27*100/29 | | 5(t-3)+3t=4(2t+4)-12 | | 300=-4a^2+80a | | 3+x/(x-3)(x+3)=0 | | 3+x/(x-3)(x+3) | | 104*23/52*3/4 | | 2+3c-5=-4 | | 5/6-4 | | 5/6(-4) | | 5/4(-4) | | 12-0.3(a-2)=0.5(11a-2) | | 17-4n=84 | | 4+-7=5 | | (x/x^2-9)+(3/x^2-9)=0 | | x/x^2-9+3/x^2-9=0 | | 26/49*21/20*8/39 | | 120*31/40*1/9 | | 8-3(2x+7)=7x-4 |